Waste Reduction for Raw Material Storage using RFID System: A Case Study of Aquatic Animal Food Factory - วรรณศิริ, อุไรวรรณ (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2018)
This paper proposes a new method to reduce waste in the counting process of raw materials using Radio Frequency Identification (RFID). A case study of Aquatic Animal Food Factory is considered to demonstrate this RFID-based approach. By using the traditional technique, the problem arose because the product labels of raw materials were susceptible to be lost or damaged during the storage process resulting in additional manpower as well as time for counting such the items. The objectives of this research were: 1) to study the raw material storage management system of the aquatic animal food factory 2) to apply the RFID system to the raw material storage of the aquatic animal food factory. The research method consisted of data collection and data analysis of the raw material storage that contributed to a waste reduction in the counting procedure. After implementing the RFID system, the resource utilization resulted from the traditional and the new approaches were compared and discussed. The study found that the traditional approach encompassed 6 steps using 16 employees per day to count the raw-material items in a warehouse. However, when the RFID technique has been set up to the system, the counting process were reduced to 3 steps using 5 employees. The manpower was decreased by 68.75% per warehouse per day. Furthermore, the proposed approach could improve the efficiency of warehousing operations in terms of data accuracy. Consequently, the production of aquatic animal food could meet the customer satisfaction even more.